Elucidation of the Structure of Lignin–Carbohydrate Complexes in Ginkgo CW-DHP by 13C-2H Dual Isotope Tracer - Kai Zhang; Yanchao Liu; Sheng Cui; Yimin Xie (Molecules, 2021)
To elucidate the chemical linkages between lignin and carbohydrates in ginkgo cell walls, 13C-2H-enriched cell wall-dehydrogenation polymers (CW-DHP) were selectively prepared with cambial tissue from Ginkgo biloba L. by feeding D-glucose-[6-2H2], coniferin-[α-13C], and phenylalanine ammonia-lyase (PAL) inhibitor. The abundant detection of 13C and 2H confirmed that D-glucose-[6-2H2] and coniferin-[α-13C] were involved in the normal metabolism of ginkgo cambial cells that had been effectively labelled with dual isotopes. In the ginkgo CW-DHP, ketal and ether linkages were formed between the C-α of lignin side chains and carbohydrates, as revealed by solid state CP/MAS 13C-NMR differential spectroscopy. Furthermore, the DMSO/TBAH ionic liquids system was used to fractionate the ball-milled CW-DHP into three lignin-carbohydrate complex (LCC) fractions: glucan–lignin complex (GL), glucomannan–lignin complex (GML), and xylan–lignin complex (XL). The XRD determination indicated that the cellulose type I of the GL was converted into cellulose type II during the separation process. The molecular weight was in the order of Ac-GL > Ac-GML > XL. The 13C-NMR and 1H-NMR differential spectroscopy of 13C-2H-enriched GL fraction indicated that lignin was linked with cellulose C-6 by benzyl ether linkages. It was also found that there were benzyl ether linkages between the lignin side chain C-α and glucomannan C-6 in the 13C-2H-enriched GML fraction. The formation of ketal linkages between the C-α of lignin and xylan was confirmed in the 13C-2H-enriched XL fraction.